1976
DOI: 10.1177/0310057x7600400207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diazepam on Neuromuscular Transmission and its Interaction with Non-Depolarizing Muscle Relaxants

Abstract: Sl'~nL\\{Y-,"cltroll/ltsclIlar !Jlockillg actiolls of dia:;cpam awi its interaction with some myonellral h/ockillg agents 7cere stw/ied ill dogs and /1/ humalls undcrr;oillg surgery under r;cneral allllcsthcsia. J)iazepillll alonc had 110 effect Oil the response of tibialis anterior 1Iluscle to illdirt'Ct stimulatioll in dor;s. Ar;aill, diazepam ill a bolus dose of 5 mg did not illfluence a prc-c.ristillr; partial bloc/, hy d-tllhocllrarine, gallamine or panCl/rOllilllll. Bl/t a significallt ill crease ill bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In 1970, Feldman and Crawley [123] suggested that diazepam interacted with muscle relaxant drugs. Diazepam alone has no effect on the response of the tibialis anterior muscle to indirect stimulation in dogs and, in a bolus dose of 5 mg, does not influence a pre‐existing partial block by tubocurarine, gallamine or pancuronium [124]. The degree and duration of block by tubocurarine was not affected significantly by simultaneous administration of diazepam in man.…”
Section: Post‐synaptic Effectmentioning
confidence: 99%
“…In 1970, Feldman and Crawley [123] suggested that diazepam interacted with muscle relaxant drugs. Diazepam alone has no effect on the response of the tibialis anterior muscle to indirect stimulation in dogs and, in a bolus dose of 5 mg, does not influence a pre‐existing partial block by tubocurarine, gallamine or pancuronium [124]. The degree and duration of block by tubocurarine was not affected significantly by simultaneous administration of diazepam in man.…”
Section: Post‐synaptic Effectmentioning
confidence: 99%